(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article analyzes the dynamics of students’ personal characteristics during unstable and stable periods of adaptation to higher education. The study examines changes in personal attributes—such as adaptive behavior, stress tolerance, motivation, social adjustment, and psychological stability—throughout the adaptation process. It describes how personal characteristics undergo dynamic shifts during the unstable period (the initial stage of adjustment to the new learning environment) and the stable period (the stage in which the student becomes integrated into the academic process), and it offers recommendations for improving adaptation and reducing stress. The findings have practical relevance for pedagogical and psychological support services in higher education institutions.